Bovine viral diarrhea virus (BVDV) genetic diversity in Spain: A review - Francisco J. Diéguez; Manuel Cerviño; Eduardo Yus (Spanish Journal of Agricultural Research, 2017)
Bovine viral diarrhea virus (BVDV), a member of the genus Pestivirus of the family Flaviviridae, causes significant losses in cattle farming worldwide because of reduced milk production, increased mortality of young animals and reproductive, respiratory and intestinal problems. The virus is characterized by an important genetic, and consequently antigenic and pathogenic diversity. Knowing the variability of viral strains present in a population provides valuable information, particularly relevant for control programs development, vaccination recommendations and even identification of likely infection sources. Such information is therefore important at both local and regional levels. This review focuses on the genetic diversity of BVDV isolates infecting cattle in Spain over the last years. According to the published data, the most prevalent BVDV group in Spain was 1b, and to a lesser extent 1d, 1e and 1f. Besides, BVDV-2 has also been found in Spain with several ratified isolates. The studies carried out in Spain also showed increased genetic heterogeneity of BVDV strains, possibly due to a more intensive use of analytical tools available, presenting studies with increasingly greater sample sizes.